'Equally at home on Beacon Hill and Hill 16'? Transnational identities among Irish‐born return migrants from the United States. (10th January 2014) - RALPH, DAVID
Abstract In this article, I examine the transnational identities that return migrants create upon resettlement in their country of origin. Specifically, I draw on interviews with Republic of Ireland‐born return migrants from the United States between the years 1996 and 2006. The analysis shows that return migrants – like other migrant groups – maintain and establish translocal identities and practices that straddle 'here' (Ireland) and 'there' (United States) upon return. However, the article goes further, asking why returnees develop such border‐spanning social fields. Some recent scholarship suggests that some migrants develop transnational identities as an adaptive response to a hostile receiving society. The analysis here shows a similar process at play for certain return migrants in the post‐return environment. Doubtless, for some returnees, a transnational identity is a natural outgrowth of having spent several years in the United States. Yet for others, one can better explain this transnational identity as a coping strategy to buffer resettlement anxieties and disappointments.